Instytucjonalne formy wsparcia młodzieży pochodzącej z rodzin dysfunkcyjnych na przykładzie działań środowiska Uniwersytetu Ekonomicznego w Katowicach - Polok, Grzegorz (Studia Pastoralne, 2026)
The results of the study show that over 40% of the University of Economics in Katowice (UEKat) students grew up in dysfunctional families, mainly burdened with alcoholism. This leads to personality problems during high school education. To challenge this issue the University offered several supportive actions, e.g.: adaptation day lecture “Efficient studying and dysfunctional family”; sharing a guidance book “Spread your wings”; mandatory classes in addiction prevention “Correction” and daily duty hours of psychologist. Activities of the academic chaplaincy “Zawodzie” complement these actions. The chaplaincy organizes a year-long therapy for students of dysfunctional families and offers them pastoral care. The preventive and supportive solutions dedicated to the students of UEKat seem to be a model scheme for other academic communities.